2011
DOI: 10.1021/jp1121454
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Tunneling Microscopy Investigation of Substrate-Dependent Adsorption and Assembly of Metallofullerene Gd@C82 on Cu(111) and Cu(100)

Abstract: The structural and electronic properties of Gd@C82 adsorbed on Cu(111) and Cu(100) surfaces were investigated by scanning tunneling microscopy (STM). STM images showed that the lattice structure of the underlying metal substrates affected the arrangement of the metallofullerene molecules. Preferred adsorption orientations of the molecules were found from STM images with submolecular resolution. Differences in the scanning tunneling spectroscopy of molecules adsorbed on Cu(111) and Cu(100) were observed and att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…Further studies showed that Gd@C 82 (OH) 22 nanoparticles maintained their optical transparency and remained within a constant size range over a period of 1 month in physiological media, and no significant release of Gd 3+ ions was detected by inductively coupled plasma-mass spectrometry within 6 days, indicating the intrinsic stability of Gd@C 82 (OH) 22 nanoparticles [11,13]. Some unique physicochemical properties of Gd@C 82 (OH) 22 nanoparticles have also been examined in subsequent studies [19][20][21].…”
Section: Characterizationmentioning
confidence: 98%
“…Further studies showed that Gd@C 82 (OH) 22 nanoparticles maintained their optical transparency and remained within a constant size range over a period of 1 month in physiological media, and no significant release of Gd 3+ ions was detected by inductively coupled plasma-mass spectrometry within 6 days, indicating the intrinsic stability of Gd@C 82 (OH) 22 nanoparticles [11,13]. Some unique physicochemical properties of Gd@C 82 (OH) 22 nanoparticles have also been examined in subsequent studies [19][20][21].…”
Section: Characterizationmentioning
confidence: 98%
“…In addition, metallofullerenes, as higher temperature superconductors, redox active systems, and contrast agents etc., have been investigated. 14,15,[33][34][35][36][37][38][39][40] However, the properties and structures of fullerenes can be significantly altered by metal inside the carbon cage. [33][34][35][36][37][38][39][40] The synthetic amount of metallofullerenes is also far less than fullerenes.…”
Section: Introductionmentioning
confidence: 99%
“…They can contain clusters that bear great potential when it comes to the production of molecular arrays on surfaces. Many of them are particularly stable, survive sublimation and may be easily imaged 16,17 and manipulated with scanning probes 18,19 . While the R=holmium or terbium based R 3 N@C 80 species showed non-collinear paramagnetism 20 , it was recently found that the isotropic gadolinium R 3 species, shows ferromagnetically coupled collinear paramagnetic behaviour 21 .…”
mentioning
confidence: 99%